Uresničevalec vatikanske "vzhodne politike" papeža Pavla VI. - Reher, Srečko (Časopis za zgodovino in narodopisje, 2020)
Vekoslav Grmič was an excellent professor at the Theological Faculty, teaching the courses Theological Foundations for Dialogue and Modern Atheism. Both courses covered a broad spectrum of dialogue in all levels, but mostly with unbelievers - atheists, members of other religions, and challenges of the modern world. He did not deal with dialogue only on the theoretical level, but it became his way of living according to his bishop motto Announce the Gospel. He also built his critical theological thought on the Gospel, and his ideas are still relevant and challenging today.
Keywords: ateisti; atheists; Christian Socialism; contextual theologies; dialog med človekom in Bogom; dialog med človekom in svetom; dialog med verujočimi in neverujočim; dialogue between a person and the world; dialogue between believers and unbelievers; dialogue between humans and God; East politics; evangelical Christianity; evangelijsko krščanstvo; Grmič, Vekoslav; Juridicism; juridizem; kontekstne teologije; Ostpolitik; pokonstantinovsko krščanstvo; Post-Constantine Christianity; religious fundamentalism; teologija socializma; verski fundamendalizem; vzhodna politika